Wideband Ultrasonic Acoustic Underwater Channels: Measurements and Characterization. - López-Fernández, Jesús Manuel; Fernández-Plazaola, Unai; París-Ángel, José Francisco; Díez-del-Río, Luis; Martos-Naya, Eduardo (IEEE, 2020)
In this work we present the results of a measurement campaign carried out in the Mediterranean sea aimed at characterizing the underwater acoustic channel in a wideband at ultrasonic frequencies centered at 80 kHz with a width of 96 kHz, covering two octaves from 32 to 128 kHz. So far, these type of wideband measurements are not found in the literature. Periodic orthogonal frequency division multiplexing (OFMD) sounding signals using Zadoff-Chu sequences have been specially designed for this purpose. The collected data has been post-processed to estimate the time-variant impulse and frequency responses and relevant parameters for system design like the time coherence, bandwidth coherence, delay spread and Doppler bandwidth. The statistical behavior of the channel gain random fluctuation has also been analyzed. This information has been extracted for both the global channel and each path separately. The wide bandwidth of the measurements have allowed the characterization of the channel in a scarcely explored ultrasonic band with an accuracy that is far beyond what is reported in previous works.
https://journals.ieeeauthorcenter.ieee.org/become-an-ieee-journal-author/publishing-ethics/guidelines-and-policies/post-publication-policies/#submitted
Keywords: Acústica submarina; Sistemas de telecomunicaciones; Sea measurements; Channel estimation; Underwater Acoustic Communications (UAC); Underwater ultrasonic channels; Shallow water acoustic channel